Pengaruh Penerapan Model Discovery Learning Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP - Pitriani, Laili; Hayati, Laila; Azmi, Syahrul (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the differences and the Effect of the influence of the Discovery Learning model on the mathematical communication skills of grade VIII students at SMPN 11 Mataram in the academic year 2025/2026. This study is an experimental study with a quasi-experimental posttest only control group design. The research population consisted of grade VIII students at SMPN 11 Mataram, with sample classes VIIIA as the experimental class and VIIIB as the control class, selected through cluster random sampling. Data collection techniques used mathematical communication ability test instruments. Before conducting data analysis, prerequisite tests were carried out, including normality and homogeneity tests. The main data analysis was performed using the Independent Samples t-test and effect size calculations. The results showed that: 1) The average mathematical communication ability score in the experimental class was 78.4, which was higher than that in the control class, which was 67.4; 2) There was a difference in the average mathematical communication ability scores between students in the experimental class and those in the control class, with an effect size of d = 0.82, which is classified as large. In conclusion, the application of the Discovery Learning model has an effect on the mathematical communication ability of grade VIII students at SMPN 11 Mataram in the academic year 2025/2026.